The culture of banana cultivation: an exploratory study of a local banana seed system in Central Uganda. - Kilwinger, Fleur B.M.; Rietveld, Anne M.; Almekinders, Conny J.M. (2017)
Banana is one of the most important staple crops in Central Uganda. In central Uganda most of the bananavarieties cultivated belong to the East African Highland Bananas (EAHB) which include food (Matooke) and beer (Mbidde) varieties. The production of banana in Central Uganda has declined over the last years due to soil exhaustion, pest pressure and socio-economic constraints. Besides that new pests and diseases have entered the country in recent years. One of those diseases is Banana Xantomonas Wilt (BXW) which can destroy entire banana plantations. Farmers obtain new planting material mainly "informal" from their own farms or from fellow farmers. This contributes to built-up and rapid spread of diseases. Tissue Culture (TC) banana plantlets have been promoted and distributed to combat these negative effects of the current type of acquisition of planting material. Despite efforts the adoption of improved banana varieties and TC banana plantlets remains low under small-holder famers in Central Africa. The aim of this research is to get a better understanding of the current banana seed system in order to make future interventions, aiming to improve the seed system, better suited to farmers' needs. The focus of the research has been on the use of banana variety and the selection, sources and availability of planting material. The study was conducted in Mukono district of Uganda were smallholder banana farmers are common. In these regions the use of TC banana plantlets has been promoted by the governments National Agricultural Advisory Services (NAADS) and the International Institute of Tropical Agriculture (IITA). During the study the role of TC banana plantlets in the banana seed system has been addressed. To understand how new diseases affect the seed system the effects of BXW on seed sourcing practices among farmers were also examined.